Characterization of Patients with Uncontrolled Arterial Hypertension in Relation to Adherence to Treatment - Yadelaicy Ochoa González; Yoenny Peña García; Joanne Mola Vega (Revista Finlay, 2022)
Background: the treatment and control of hypertension have improved in recent years, but adherence to treatment is still poor. Objective: to characterize patients with uncontrolled hypertension, in relation to adherence to treatment, in a family doctor's office in Puerto Padre, Las Tunas. Methods: a descriptive cross-sectional study was carried out in office 2 of a Health Area in the Puerto Padre municipality, Las Tunas province, in April 2022. The study population consisted of 232 hypertensive patients, and the sample, by 86 patients with uncontrolled arterial hypertension. The variables analyzed were: age, sex, level of education, occupation, per capita family, psychosocial risk factors, time of evolution of the disease, time and adherence to treatment. To obtain the information, an interview questionnaire was designed, in which the Morisky-Green Test questions were included. Absolute frequencies and percentages were used for the analysis. Results: the female sex prevailed (62.8 %) and those over 50 years old (67.4 %), the level of pre-university or medium technical education (39.5 %), 30.2 % were workers and 24.4 % were retired. In the psychosocial risk factors, stress prevailed (70.9 %). Of the patients, 21 (24.4 %) had been diagnosed for between 8 and 11 years and more than 15 years, and 27.9 % had received treatment for more than 15 years. 69.8 % do not have adherence to the treatment of arterial hypertension. Conclusions: women, those over 50 years of age and psychosocial factors such as stress, anxiety and depression prevailed, mostly with more than 15 years of diagnosis and treatment. Cases of patients not adhering to antihypertensive treatment predominated.